Kouroura unipartita Anderson, a new genus and species from French Guiana related to the Colombian genus Koreguajus Anderson and Bermúdez (Coleoptera: Curculionidae: Dryophthorinae: Sphenophorini) - Anderson, Robert S. (Zootaxa, 2026)
Kouroura unipartita Anderson (Coleoptera: Curculionidae: Dryophthorinae; Rhynchophorini), a new genus and species is described based on a single male from near Kourou, French Guiana. The genus is distinguished from the related genus, Koreguajus Anderson and Bermúdez from Colombia, by the antennal funicle with a single article, subapically strongly tumescent pygidium, elongate very narrow scutellar shield, and subbasally impressed pronotal disc. Kouroura and Koreguajus are here proposed to constitute a a monophyletic lineage within Sphenophorini, defined by the character states of antenna with the article(s) tightly connected, wider than long, funicular articles subequal in width to club; pilose area of club visible only as a small apical patch; appendages (including dorsum of robust tarsomeres) and most of body covered with fine micropilosity. At present, no formal name is assigned to this lineage.